Project-Based Learning with STEM Approach in Automotive Engineering: A Study of Increasing Students' 21st Century Skills - Giok Ade Surti; Putu Sudira; Farid Mutohhari; Suyitno Suyitno; Muhammad Nurtanto (Jurnal Pendidikan dan Pengajaran, 2022)
The weakness of 21st century skills in vocational education students, especially in the automotive department, is a big polemic that needs to be solved. Organizing project-based learning is a strong solution in improving 21st century skills in students. Moreover, the integration of the STEM approach allows collaboration between various disciplines at once. This study analyses the implementation of project-based learning with a STEM approach (PjBL-STEM)to improve 21st century skills through. A quasi-experimental study using a nonequivalent control group design was used by involving 214 vocational education students as the research sample. The data generated are in the form of the concept and implementation of PjBL-STEM and the value data from the observation of 21st century skills which are measured using the observation method. Data analysis involved paired sample t-test and independent sample t-test preceded by normality and homogeneity tests. The results showed that the PjBL-STEM model was proven to improve 21st century skills based on the paired effect of pretest to posttest and the difference in the posttest mean of the experimental class was higher than the control class. These results become recommendations, especially in vocational education in order to improve 21st century skills which are currently an important qualification in the world of work, equipping students with multi-competence, because it integrates various disciplines.